Preparation of spent fluid catalytic cracking catalyst-metakaolin based geopolymer and its process optimization through response surface method. (20th December 2020) - Zhang, Ruobing; Liu, Tao; Zhang, Yimin; Cai, Zhenlei; Yuan, Yizhong
Highlights: SFCC catalyst is used to partially replace metakaolin to prepare geopolymer. RSM optimized parameters make the SMBG compressive strength higher than 40 MPa. SFCC catalyst can be partially dissolved and participate in geopolymerization. Reduce SFCC catalyst particle size can make it better in geopolymerization reaction. Abstract: In this study, spent fluid catalytic (SFCC) catalyst was used to prepare geopolymer as a replacement of metakaolin. Through the response surface experiment method, the single-factor influence degree and interactive influence degree of the content, alkali content and water content of SFCC catalysts as well as the particle size of SFCC catalysts on the compressive strength of geopolymers were analyzed. According to the quadratic model, the replacement of metakaolin with an appropriate amount of SFCC catalyst will improve the compressive strength of the geopolymers, but the replacement of metakaolin with an excessive amount of SFCC catalyst will weaken the compressive strength of geopolymers. a highest compressive strength of 41.22 MPa was obtained with the 20% replacement of SFCC catalysts, which was 21.6% higher than the geopolymer without SFCC catalyst. The microstructure and crystal structure analysis indicated that SFCC catalyst partially participated in the geopolymerization.